Dengue Hemorrhagic Fever in North Minahasa Regency in 2021-2022: Study Epidemiological - Ottay, Ronald Immanuel; Sapulete, Ivonny Melinda; Sapulete, Margareth Rosalinda; Sumampouw, Oksfriani Jufri; Nelwan, Jeini Ester (MultiTech Publisher, 2024)
Dengue Hemorrhagic Fever (DHF) is a disease that rapidly spreads, particularly in tropical and subtropical regions. One of the places affected by DHF cases is North Minahasa Regency, which is one of the top donors to cases in North Sulawesi Province. The purpose of this study is to describe the prevalence of DHF in North Minahasa Regency between 2021 and 2022 in terms of time, place, and person. This is a quantitative descriptive study. This study employed secondary data. This data was collected from the North Minahasa Regency Health Office. Data will be collected from July to October 2023. The data collected were examined univariately. The data showed that the most DHF cases occurred in 2022, with an increase in incidence in March and November. Furthermore, DHF cases were prevalent in Dimembe District (working area of Tatelu Health Center), Kauditan District (working area of Kauditan Health Center), Talawaan District (working area of Talawaan Health Center), Airmadidi District (working area of Airmadidi Health Center), and Kalawat District (working area of Puskesmas Kolongan). The prevalence of DHF cases in 2021-2022 was higher in men, with a total of 150 cases and an average of 76 instances. DHF incidences increased in 2021, particularly in February, August, and December. It can be determined that the largest frequency of DHF in North Minahasa Regency in 2021-2022 occurs between February-March and November-December, were identified in Dimembe District, and the majority of the DHF cases are male